Dampak Keseimbangan Hidup-Kerja dan Tuntutan Tugas pada Efisiensi Tenaga Kerja Operator PT. Mutiara Mulia Raya (MMR) di Tenggarong Seberang (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
The mining industry is inherently associated with high-risk environments and intense job stress, particularly for heavy equipment operators who often face extended work hours, challenging physical conditions, and heavy workloads. This study aims to analyze the influence of work-life balance and workload demands on employee productivity at PT. Mutiara Mulia Raya (MMR), a subsidiary of one of Indonesia's leading mining contractors. Using a quantitative descriptive approach, data were collected through saturated sampling involving 76 operational employees. Data analysis was conducted through multiple regression to determine the partial and simultaneous effects of the independent variables. Findings reveal that work-life balance has a significant positive effect on productivity, suggesting that employees who can harmonize their professional and personal lives tend to perform more effectively. Additionally, workload also has a significant influence, with excessive task demands negatively affecting efficiency and increasing the risk of fatigue. The integration of real-time monitoring technology, such as the OPA PAMA Smartwatch system, offers the potential to optimize scheduling and enhance productivity. However, overly strict implementation may trigger psychological pressure and disrupt employees' sense of autonomy. This study highlights the necessity for mining companies to adopt a holistic approach to human resource management that incorporates both psychological well-being and operational performance. Strategic policies that promote flexibility, monitor employee fatigue, and support personal well-being can foster greater workforce productivity and reduce occupational risks. The findings underscore the importance of balancing operational demands with employee welfare to ensure sustainable productivity in high-risk industries.